PENGARUH PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE “GIVING QUESTION AND GETTING ANSWERS“ TERHADAP HASIL BELAJAR DASAR-DASAR KELISTRIKAN SISWA DI KELAS X TEKNIK AUDIO VIDEO SMK NEGERI 1 BUKITTINGGI - Gladiska Yunis; Yasdinul Huda; Dedy Irfan (Universitas Negeri Padang, 2014)
The problem in this research is the fact that found in SMK N 1 Bukittinggi, there are many students of class X Audio Video Engineering is result study of learning outcomes below the minimum standard (KKM) in the subject Fundamentals of electricity at school set is set 75. Total students that are under KKM 60.35% and students those are above KKM 39.65%. Many factors that affect it, those are internal factors and external factors, as well as the learning model. This study aims to prove the existence of differences in learning outcomes using learning Active Learning Model Type